Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor. (June 2023) - Hsieh, Chen-Che; Yu, Shu-Han; Cheng, Kai-Wen; Liou, Yu-Wei; Hsu, Cheng-Chih; Hsieh, Chang-Wei; Kuo, Chia-Hung; Cheng, Kuan-Chen
Graphical abstract: Solid-state fermentation for C. formosanum sprouts and metabolites analysis. Highlights: Fermentation of Chenopodium formosanum sprouts by Rhizopus oligosporus was studied. Solid state fermentation of djulis in bioreactor led to more antioxidant activity. Over twenty new metabolites were found from the bioreactor system. Interactions between djulis and fungi generated seven new peptides. Bioinformatics approaches predicted two peptides with potentially high bioactivity. Abstract: The study utilized fresh fourth-day Chenopodium formosanum sprouts as the substrate for Rhizopus oligosporus fermentation. The resultant products showed higher antioxidant capacity than those from C. formosanum grains. Compared to traditional plate fermentation (PF), fermentation in a bioreactor (BF) (35 °C, 0.4 vvm aeration at 5 rpm) led to higher free peptide content (99.56 ± 7.77 mg casein tryptone/g) and enzyme activity (amylase, glucosidase, and proteinase are 2.21 ± 0.01, 54.57 ± 10.88, and 40.81 ± 6.52 U/g, respectively) than traditional plate fermentation (PF). Using mass spectrometry analysis, two peptides TDEYGGSIENRFMN and DNSMLTFEGAPVQGAAAITEK were predicted to possess high bioactive properties as DPP IV and ACE inhibitors. Additionally, over twenty new metabolites (aromatics, amines, fatty acids, and carboxylic acids) were discovered in the BF system compared to its PF counterpart. Results suggest that using a BF system to ferment C. formosanum sprouts is an appropriate method to scale-up fermentation and enhance nutritional values as well as bioactivities.